Assessing heterogeneity in factors influencing three-wheeled motorized rickshaws crash outcomes between weekdays and weekends - Zia Ur Rehman; Jiang Chaozhe; Emmanuel Kofi Adanu; Arshad Jamal; Yahya Almarhabi; Md Kamrul Islam; Hassan M. Al-Ahmadi (Scientific Reports)
Abstract Traffic crashes involving three-wheeled motorized rickshaws (3-WMRs) pose considerable public health risk in developing countries. Although prior research has thoroughly investigated the effects of risk factors such as weather, road conditions, and driver characteristics on 3-WMR collisions, the effect of the day of the week (weekday versus weekend) has been relatively underexplored. The study uniquely identifies the temporal heterogeneity in 3-WMR injury severity risk factors between weekday and weekend crashes. By integrating psychological and sociological theories, it also aims to understand how risk perception and sensation seeking behaviors contribute to various injury outcomes in 3-WMR crashes. The current study aims to fill this gap by investigating the risk factors contributing to injury severity in such crashes, employing a random parameters multinomial logit model with heterogeneity in means and variance. The study conducted an empirical analysis using traffic crash data spanning six years (2017–2022) from RESCUE 1122 in Rawalpindi, Pakistan. The findings identify several statistically significant factors that influence major injuries, including single-vehicle crashes, teenage drivers, rainy weather, peak traffic hours, wrong U-turns, speeding, and driver distraction. The study’s findings demonstrated the importance of considering temporal heterogeneity, thereby offering differentiated policy recommendations for weekends and weekdays, ensuring more tailored and effective safety interventions for 3-WMR users.